1992
DOI: 10.1128/mcb.12.6.2653
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cdc25 antibodies inhibit guanyl nucleotide-dependent adenylyl cyclase of Saccharomyces cerevisiae and cross-react with a 150-kilodalton mammalian protein.

Abstract: The CDC25 gene product of the yeast Saccharomyces cerevisiae has been shown to be a positive regulator of the Ras protein. The high degree of homology between yeast RAS and the mammalian proto-oncogene ras suggests a possible resemblance between the mammalian regulator of Ras and the regulator of the yeast Ras (Cdc25). On the basis of this assumption, we have raised antibodies against the conserved C-terminal domain of the Cdc25 protein in order to identify its mammalian homologs. Anti-Cdc25 antibodies raised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…2A). These findings are in agreement with a previous report that analyzed endogenous CDC25 protein in wild-type cells (18). Of potential biological significance, but irrelevant to the issue at hand, we found that the level of expression of full-length CDC25 was considerably lower than that of any of the deletion mutants that lacked residues 1 to 877 (Fig.…”
Section: Resultssupporting
confidence: 83%
“…2A). These findings are in agreement with a previous report that analyzed endogenous CDC25 protein in wild-type cells (18). Of potential biological significance, but irrelevant to the issue at hand, we found that the level of expression of full-length CDC25 was considerably lower than that of any of the deletion mutants that lacked residues 1 to 877 (Fig.…”
Section: Resultssupporting
confidence: 83%
“…Total-protein extracts were prepared following cell breakage using glass beads (21) or the Y-Per reagent (Pierce). Cells were broken with glass beads (0.4 to 0.6 mm in diameter) by vigorous vortexing in ice-cold buffer containing 100 mM HEPES (pH 8.0), 1% sodium dodecyl sulfate (SDS), 1% 2-mercaptoethanol, 5 mM EDTA, 10% glycerol, 2% Triton X-100, and a protease inhibitor mixture (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…Proteins were transferred to nitrocellulose using a semi-dry blotter (LKl3). The blot was blocked for 1 h at room temperature with Tris-buffered saline containing 5% powdered skimmed milk (Cadbury), 0.02% NaN, and 0.3% Tween 20 and reacted overnight in the same solution with immunopurified anti-Cdc25 antibody diluted 1 : 40 [26]. Specific blocking of the antibody was carried out by a l-h incubation at room temperature with a cell lysate prepared from E. coli expressing the C-terminus of Cdc25 against which the antibody was raised.…”
Section: Western Blottingmentioning
confidence: 99%
“…We have checked the expression of the gene CSC25 in strain cdc25'"[CSC25, 2 p] at three different temperatures by using polyclonal anti-Cdc25 antibodies [26] as described in Materials and Methods. As shown in Fig.…”
Section: Expression Of the Csc25 Genementioning
confidence: 99%
See 1 more Smart Citation